STUDI KASUS PESERTA DIDIK BERPERILAKU HIPERAKTIF DI SMA NEGERI 1 SUNGAI RAYA - Sisca Dwi Septiarini; Muhammad Asrori; Luhur Wicaksono (Universitas Tanjungpura, 2022)
AbstractThis study aims to identify and alleviate the case of students who behave hyperactively at State Senior High School 1 Sungai Raya. Case Subjects in this study were students of class XI who experienced hyperactive behavior with 2 case subjects. This study uses a qualitative approach with descriptive methods in the form of case study research. This study uses interview data collection tools and home visits. From the results of this study, the characteristics of students who behaved hyperactively experienced by the subject of case I were not focused, liked to say rude things, did not want to give in, often made their own decisions. While the characteristics experienced by the subject of case II are often disturbing friends, making chaos during the learning process, leaving class, getting angry easily. The factors that cause students to behave hyperactively are (1) Family, (2) Loneliness, (3) Less interest in learning. To overcome the problems experienced by the subject of case I used a Behavioral model approach with Assertive Exercise Techniques and Positive Reinforcement, and for Subject II used a Behavioral model approach with Response Formation and Pilot Techniques. The role of the counseling guidance teacher is to monitor the development of students by collaborating with subject teachers and parents.Keywords: Behavioral Counseling, Hyperactive Behavior